Two new species of brackish-water Macrostomum (Platyhelminthes, Macrostomida) from southern China - Fang, Chu-Yu; Wang, Lei; Zhang, Yu; Wang, An-Tai (Zootaxa, 2016)
Two new species of brackish-water Macrostomum (M. zhujiangensis n. sp. and M. baoanensis n. sp.) were described based on samples collected from the littoral zone of the Zhujiang Estuary. These are the first records of brackish-water Macrostomum from southern China. Macrostomum zhujiangensis n. sp. and M. baoanensis n. sp. differ from other similar species in the length and morphology of the penis stylet.  The penis stylet of M. zhujiangensis n. sp. is C-shaped and its distal opening has a beveled edge. The penis stylet of M. baoanensis n. sp. is J-shaped and the distal region is thicker than other parts of the penis stylet. Molecular phylogenetic analysis supports the establishment of the new species.